Functional Changes Induced by Orexin A and Adiponectin on the Sympathetic/Parasympathetic Balance - Messina, Antonietta; Monda, Marcellino; Valenzano, Anna; Messina, Giovanni; Villano, Ines; Moscatelli, Fiorenzo; Cibelli, Giuseppe; Marsala, Gabriella; Polito, Rita; Ruberto, Maria; Carotenuto, Marco; Monda, Vincenzo; et al. (Frontiers in Physiology, 2018)
Obesity and lifestyle-related diseases are major problems faced by people in developed nations. Although exercise training prevents the progression of diabetes and obesity, the motivation for exercise is generally low in obese animals and humans. The autonomic nervous system (SNA) plays a crucial role in the regulation of eating behavior. Moreover, the SNA is involved in the body temperature regulation that is strictly related to body weight control, in accordance with the "thermoregulatory hypothesis" of food intake. Some neuronal peptides and hormones, like orexins and adiponectin, are also involved in the regulation of locomotion activity as well as food intake and metabolic rate. Furthermore, adiponectin as well as orexin A are involved in the control of body temperature, food intake and therefore in obesity-related diseases. The aim of this study was to investigate the changes in body temperature (Tc), and heart rate (HR) after an intracerebroventricular (ICV) injection of orexin A and adiponectin in animal model. The results of this study show that the orexin A levels are likely involved in the increase of Tc and HR. It is also clear that there is not a correlation between these parameters and adiponectin levels. Further studies are needed to assess adiponectin actions and outcome in the central nervous system in terms of energy expenditure, body temperature, heart rate and physical activity performance regulation.